Correlación de las pruebas de susceptibilidad a la caries: recuentos de lactobacilos y candida en niños escolares de 9 a 11 años en Caldas, Antioquia, Colombia - Luz Ines Sierra; Maria del Socorro Estrada; María Elena Galeano; Diana Maria Gaviria; Patricia Alvarez; Beatriz Restrepo; Carlos Mario Parra; Luz Elena Lopera (Universidad de Antioquia, 1995)
In the present work we studied, the correlation betwen sucrose intake and caries (DFs), in 195 school children between the age of 9 to 11 years old from Caldas, Antioquia, Colombia. In the same sample, parallel works were conducted to study salivary buffer capacity, "mutans" Streptococci, and sucrose intake. This population didn't have fluoride in the water supply, but have preventive annual program of topical fluoride, a regular oral higiene (Plaque index 1.35) and high caries scores (DFs = 13.6). The salivary Lactobacilli counts were positive (>1^5 CFU/ml) in 2 thirds of the sample. Our results didn't show correlation between de DFs score and Lactobacilli salivary counts and either between Candida salivary counts. Only 14.2% of the children had Candida in saliva. The correlation between these results and the parallel studies had shown low correlation in the high DFs score group, between sucrose intake and the salivary Lactobacillus counts. None of these show correlations with Streptococcus of "mutans" group counts or buffer capacity.